Face Tracker Audio for Saronen Music Using Augmented Reality on Social Media - Ahmad Walid Hujairi; Khoironi Khoironi; Much Chafid; Ahmad Khairul Umam; Ahmed David Anugerah (Jurnal Teknologi Informasi dan Terapan, 2025)
Saronen music is a traditional Madurese music commonly played at cultural and traditional events. Saronen music typically combines traditional instruments such as gamelan, trumpet, kenong, korca, large drums, and small drums, producing a unique sound characteristic of Madura. This research aims to preserve saronen music through the development of an interactive filter on Instagram and Facebook using augmented reality. The face tracker feature allows users to interact with each instrument using head movements or facial expressions. The development method, MDLC encompasses concept, design, material collection, design, testing, and distribution. Functional research results indicate the filter can run well on Android and iOS operating systems. Testing on 31 social media users yielded positive feedback from the majority, stating that the filter has clear instructions, a low error rate, is easy to use, satisfying, and attractive. This innovation is expected to be a means of preserving saronen music for the younger generation through social media.